A macroscopic analysis of the demographic impacts of flood inundation in Thailand (2005–2019) - Tsuda, Hinako; Tebakari, Taichi (Progress in Earth and Planetary Science, 2023)
In Thailand, floods are occurring more frequently due to climate change, and recent economic development and population growth may have altered the way in which people interact with floods, including migration to other regions. In this study, we analyzed the relationship between flooding and population distribution across Thailand from 2005 to 2019 to improve measures for minimizing flood damage. We used population distribution point data from 2009 to 2019 produced by Oak Ridge National Laboratory to analyze trends in population movement and distribution, by examining whether population sizes were greater than, less than, or equal to estimated values in regions throughout Thailand. The results suggest that floods in 2011 and 2017 caused temporary migration to areas that were not inundated or to the metropolitan Bangkok area. Flood responses changed after the 2011 floods, which have been described as the worst flood in Thai history. Next, we examined the relationship between the number of regions with lower than estimated population and flood data for the previous year including precipitation, inundated area, and deaths caused by flooding. Inundation area had a significant impact on population decline, with correlation coefficients of 0.426 and 0.501 for the north and northeast, respectively. The number of deaths caused by flooding in a given year also led to a population decline in the following year. However, precipitation did not exhibit the same trend. Therefore, population demographics after floods have shown regional characteristics in recent years, with Thai people shifting from a flood-tolerance lifestyle to a flood-avoidance lifestyle, mainly in local urban areas and the metropolitan Bangkok area.